Our life with plastic, a review of plastic product abuse in the age of consumerism - Ewa Plażuk; Łukasz Zbucki (Rozprawy Społeczne)
Abstract It is estimated that up to 9 million tons of plastic waste enters the oceans every year. There is a top of research on the harmfulness of microplastics to our health. While aspects of the use of polymeric packaging for food, dishes, or plastic furniture and clothing are often dictated by economic considerations, psychological, sociological and cultural aspects can be shaped at the level of operation of healthy and rational product choices in local markets. With increased exposure to plastic in the world, the goal of the natural sciences is to develop research tools on the harmfulness of microplastics. Within the framework of social responsibility, social sciences should give recommendations in areas of social life and propose practical measures to make people aware of where microplastic comes from and how to reduce its use.